Photothermal Solid Slippery Surfaces with Rapid Self‐Healing, Improved Anti/De‐Icing and Excellent Stability. Issue 6 (3rd February 2023) - Tan, Shengda; Han, Xiao; Cheng, Shuman; Guo, Pu; Wang, Xuan; Che, Pengda; Jin, Rongyu; Jiang, Lei; Heng, Liping
Abstract: Icing phenomenon that occurs universally in nature and industry gets a great impact on human life. Over the past decades, extensive efforts have been made for a wide range of anti‐icing/deicing surfaces, but the preparation of anti‐icing/deicing interfaces that combine stability, rapid self‐healing and excellent anti‐icing/deicing performance remains a challenge. In this study, a photothermal solid slippery surface with excellent comprehensive performance is prepared by integrating cellulose acetate film, carbon nanotubes with paraffin wax (CCP). Apart from the excellent anti‐icing and deicing properties at −17 ± 1.0 °C under 1 sun illumination, the surface can further achieve deicing at temperatures as low as −22 ± 1.0 °C under infrared light. The fabricated surface also exhibits great stability when placed in harsh conditions such as underwater or ultra‐low temperature environments for over 30 days. Even when suffering from physical damage, the prepared surface can rapidly self‐repair under 1 sun illumination or near‐infrared (NIR) illumination within 16.0 ± 1.5 s. Due to the rapid and repeatable self‐healing performance, the lubricating properties of the interface material do not deteriorate even after 50 repeated abrasing‐repairing cycles. The photothermal solid slippery surface possesses wide‐ranging applications and commercial value at high latitude and altitude regions. Abstract : In this study, a solar‐assisted slippery surface integrates three main factors for anti/de‐icing materials: excellent anti‐icing/deicing properties, rapid and repeatable self‐healing properties, and excellent stability. It is envisaged that this work will provide new insights into the manufacture of stable surfaces with rapid self‐healing and excellent anti‐icing/deicing properties for effective practical applications.